2007
DOI: 10.1539/joh.49.205
|View full text |Cite
|
Sign up to set email alerts
|

Plasma n‐3 Polyunsaturated Fatty Acid and Cardiovascular Disease Risk Factors in Japanese, Korean and Mongolian Workers

Abstract: Plasma n-3 Polyunsaturated Fatty Acid and Cardiovascular Disease Risk Factors in Japanese, Korean and Mongolian Workers: Akiko NOGI, et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
5
19
0
1
Order By: Relevance
“…Diets rich in n-3 fatty acids have been shown to prevent obesity better than other subclasses of PUFA (56,116) . This effect has been reported in studies in human subjects (57,138,139) , mice (48,60) and rats (62,63,65,66,102) . In most of the animal studies lower fat deposition in subjects fed n-3 fatty acids was shown despite comparable food and energy intake among the groups (48,60,62,65,66) ( Table 1; lines 12, 33, 23, 22 and 14, respectively); therefore this effect can be related to the metabolic effects of n-3 fats.…”
supporting
confidence: 70%
“…Diets rich in n-3 fatty acids have been shown to prevent obesity better than other subclasses of PUFA (56,116) . This effect has been reported in studies in human subjects (57,138,139) , mice (48,60) and rats (62,63,65,66,102) . In most of the animal studies lower fat deposition in subjects fed n-3 fatty acids was shown despite comparable food and energy intake among the groups (48,60,62,65,66) ( Table 1; lines 12, 33, 23, 22 and 14, respectively); therefore this effect can be related to the metabolic effects of n-3 fats.…”
supporting
confidence: 70%
“…Previously, we observed that the average erythrocyte levels of n-3 PUFA were approximately 10% among Koreans, which is similar to the Japanese rate but higher than in Western populations [20,21]. The Korean National Health and Nutrition Examination survey consistently reported that Korean adults consumed higher amounts of fish (50 g/day) than did Western populations [22].…”
Section: Introductionmentioning
confidence: 68%
“…Our Mongolian patients with both HT and DM presented higher levels of BMI and insulin, a suggestive parameter of greater insulin resistance, in comparison to the Japanese patients. Furthermore, an earlier work has reported greater levels of insulin resistance in Mongolian workers than Japanese workers 21) . However, interestingly, our study showed that significant differences in CRP and CAVI between Japanese and Mongolian patients were maintained, even after adjusting for factors related to insulin resistance (e.g., BMI, HOMA-IR) and/or other factors, such as blood pressure levels.…”
Section: Discussionmentioning
confidence: 90%